RANCANG BANGUN SISTEM INFORMASI KREDIT MOTOR BERBASIS WEB - Tiodora, Augustinus; Armono, Sasa Ani (Computer Science and Industrial Engineering, 2025)
CV Mega Cakra Motor currently uses a manual motorbike credit recording system which has several obstacles such as recording efficiency, data security and effectiveness in the credit management process. This research aims to design and build a web-based information system that can increase efficiency, accuracy and security in motorbike credit management. The method used in this research is Waterfall, which consists of analysis, design, implementation and system testing stages. The results of this research show that a web-based information system can reduce recording errors, improve document monitoring, and provide easy access to motorbike credit data. With the system that has been designed, CV Mega Cakra Motor can optimize its operations and improve service to customers.